Job Demands and Stress Resilience of Gig Workforce : Implications for Performance and Burnout - Sharma, Nisha; Tiwari, Pooja; Sharma, Samarth (Prabandhan: Indian Journal of Management, 2026)
Purpose : This study explored the factors affecting gig workers in developing economies by focusing on stress resilience, mental health, and work performance of gig workers. Methodology : The study adopted a quantitative, explanatory research design employing purposive sampling. A total of 401 questionnaires were distributed via social media groups associated with gig work platforms, of which 351 were completed and returned, providing the final dataset for analysis. The instrument included established and validated scales to assess burnout, job demand, boundary management, digital overload, resilience, work engagement, gig-specific factors, and job performance via Smart-PLS. Findings : The findings revealed that job demands, together with digital overload, contributed to burnout, while job resources had a significant impact on work engagement compared to boundary management enhancement. Additionally, gig-specific factors and resilience significantly enhanced the performance of gig workers. Practical Implications : The results clearly indicated that organizations need to monitor job demands and manage digital overload to mitigate burnout among gig workers. To strengthen job resources like fair policies, optimizing work engagement, and retraining support for individual well-being, policymakers should address these issues well. Platform and HR Practitioners should introduce training modules to improve workers’ resilience and work–life balance as well as job performance. Organizations could create a healthy work environment and improve productivity by addressing these aspects. Originality : Unlike prior research on gig work, this study provided not only a theoretical understanding but also a practical perspective on the long-term consequences of gig workers’ burnout, work engagement, and job performance, while drawing attention to platform companies’ approach toward gig work. Contribution : This study contributed to extending the JD-R model by integrating elements of digital overload and job demands as antecedents influencing burnout. Resilience is an important resource, demonstrating that job resources have a significantly greater impact on performance outcomes than boundary management. The research conceptually advances the existing model.